Kajian Komposit Matrik Alumunium Untuk Kampas Rem Sepeda Motor Diperkuat Pasir Silika Hibrid (SiO2/BA/RHA) Dengan Metode Metalurgi Serbuk - Ridani, Hafiz Nopal; Sukanto, Sukanto; Rodika, Rodika (Jurnal Inovasi Teknologi Terapan, 2025)
In vehicles, it is very important for driving safety, therefore a reliable and optimal braking system is needed. This research focuses on reducing the use of asbestos by replacing it with more environmentally friendly materials. In addition, this study also aims to determine the effect of differences in material composition variations and sintering temperatures on the density value and hardness test of the composites produced. The method used to make composites from aluminum is the powder metallurgy method, with the stages of the process of preparing tools and materials, mixing powders, compassing, and sintering. The mixing of aluminum powder, silica sand, rice husk ash and bagasse ash uses a horizontal ball mill machine and uses the parameters of Ball Powder Weight Ratio (BPR) 10:1, machine rotation speed of 90 rpm and milling time of 4 hours. Meanwhile, the heat compaction process uses a two-way method of pressing with a hydraulic pump machine with a pressure reader. The hot composting process is carried out with a temperature of 350°C held for 20 minutes and the pressure variation of the two-way compression used is 600Psi. The results of the density and hardness tests show that the value is increasing with the number of matrices used. The sample with a reinforcement percentage of 12%, the highest density value was 2.498 g/cm3 and the highest hardness value was 73.66 HB.